11.5 A 512-Pixel 3kHz-Frame-Rate Dual-Shank Lensless Filterless Single-Photon-Avalanche-Diode CMOS Neural Imaging Probe - Changhyuk Lee; Adriaan J. Taal; Jaebin Choi; Kukjoo Kim; Kevin Tien; Laurent Moreaux; Michael L. Roukes; Kenneth L. Shepard (IEEE SOLID-STATE CIRCUITS SOCIETY, 2019)
Optical functional neural imaging has revolutionized neuroscience with optical reporters that enable single-cell-resolved monitoring of neuronal activity in vivo. State-of-the-art microscopy methods, however, are fundamentally limited in imaging depth by absorption and scattering in tissue even with the use of the most sophisticated two-photon microscopy techniques [1]. To overcome this imaging depth problem, we develop a lens-less, optical-filter-less, shank-based image sensor array that can be inserted into the brain, allowing cellular-resolution recording at arbitrary depths with excitation provided by an external laser light source (Fig. 11.5.1). Lens-less imaging is achieved generally by giving each pixel a spatial sensitivity function, which can be introduced by near-field or far-field, phase or amplitude masking. Since probe thickness must be less than 70μm to limit tissue damage and far-field masks are characterized by distances on the order of 200μm between the mask and the detector [2], we employ a near-field amplitude mask formed by Talbot gratings in the back-end metal of the CMOS process, which gives each pixel a diffraction-grating-induced angle-sensitivity [3]. Filter-less fluorescence imaging is achieved with time-gated operation in which the excitation light source is pulsed and pixel-level time-gated circuitry collects photons only after the excitation source has been removed.